2014
DOI: 10.1111/dme.12607
|View full text |Cite
|
Sign up to set email alerts
|

Association between the extent of urinary albumin excretion and glycaemic variability indices measured by continuous glucose monitoring

Abstract: The independent association between standard deviation and the extent of albuminuria was lost when the measures were normalized by mean glucose level. At least in terms of relative measures of glycaemic variability, we failed to demonstrate an independent association between glycaemic variability and albuminuria extent in patients with inadequately controlled Type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 30 publications
3
17
0
1
Order By: Relevance
“…Besides higher HbA1c levels, increased glycemic variability in T1D patients is associated with a higher risk of retinopathy, nephropathy, and peripheral neuropathy. [29][30][31][32] Recently, this was also demonstrated in T1D adolescents with a median age of 15.9 years. 33 Time between insulin administration and finishing consumption of the test meal was significantly increased compared to the standard effect of insulin aspart is noticeable after 10 to 20 minutes and the estimated total insulin action is 3 to 5 hours.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Besides higher HbA1c levels, increased glycemic variability in T1D patients is associated with a higher risk of retinopathy, nephropathy, and peripheral neuropathy. [29][30][31][32] Recently, this was also demonstrated in T1D adolescents with a median age of 15.9 years. 33 Time between insulin administration and finishing consumption of the test meal was significantly increased compared to the standard effect of insulin aspart is noticeable after 10 to 20 minutes and the estimated total insulin action is 3 to 5 hours.…”
Section: Discussionmentioning
confidence: 73%
“…Fluctuations in glucose levels appear to be considerably relevant with regard to long‐term diabetic complications. Besides higher HbA1c levels, increased glycemic variability in T1D patients is associated with a higher risk of retinopathy, nephropathy, and peripheral neuropathy . Recently, this was also demonstrated in T1D adolescents with a median age of 15.9 years …”
Section: Discussionmentioning
confidence: 81%
“…[4][5][6] The severity of hyperglycemia and glycemic variability are shown to contribute to the pathogenesis of complications Department of Endocrinology, Diabetes Care and Hormone Clinic, Ahmedabad, Gujarat, India such as retinopathy, peripheral neuropathy, urinary albumin excretion, cardiovascular events, and overall mortality; but the HbA1c measurement reflects only a piece of these important variables. [7][8][9][10][11][12][13][14] Numerous studies also support the association of long-term glycemic variability with an enhanced risk of micro and macrovascular complications, independent of HbA1c levels. [14][15][16] Hence in such cases, appropriate treatment decisions would be a challenge for the clinicians.…”
Section: Glucosementioning
confidence: 94%
“…There is observational evidence that postprandial and/or post‐load blood glucose is associated with all‐cause mortality , and more limited evidence that it is associated with cardiovascular events . On this basis, it has been suggested that glucose variability may play a role in the pathogenesis of cardiovascular complications in Type 2 diabetes: for example, in a cross‐sectional study, sd of glucose variability derived from continuous glucose monitoring (CGM) (see below) was associated with the presence of microalbuminuria (although this finding was no longer significant after adjustment for mean glucose) .…”
Section: Insights From Type 2 Diabetesmentioning
confidence: 99%